Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

Differential Bottom‐Up Control of Planktonic and Sedimentary Bacterial Communities by Phytoplankton and Extracellular Enzymes in an Asymmetric River Confluence - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Bing Yu; Xian Xu; Zhaotong Chen; Yushan Li; Zhiwei Zhu (Molecular Ecology, 2026)
Bacterial community dynamics underlie ecosystem functioning in river networks, yet how different bacterial lifestyles respond to bottom‐up biotic drivers under confluence‐induced hydraulics remains unclear. Here, we quantified spatial heterogeneity in free‐living (FL), particle‐associated (PA) and sedimentary (S) bacterial assemblages, coupled with phytoplankton and extracellular enzyme profiles, at the Yellow River‐Fenhe River confluence during the summer wet season. Clear habitat partitioning emerged, with stronger divergence at the water–sediment interface than between the two planktonic fractions (FL vs. PA). Hydrological source tracking showed that Fenhe River‐derived taxa dominated both water and sediment within the confluence reaches, whereas Yellow River lineages prevailed in the downstream reaches. Community assembly shifted hierarchically: homogeneous selection dominated FL assemblages but declined progressively toward PA and sedimentary fractions, while dispersal limitation intensified in tandem with niche contraction. Multivariate analyses showed that in addition to physicochemical factors, enzyme activity is the strongest factor predicting FL communities, explaining 43.6% of variability, whereas the phytoplankton community best predicted PA communities (68.8%). Sedimentary communities correlated weakly with phytoplankton associations (21.8%) and showed no significant link with enzyme activity. Our findings identify phytoplankton communities and enzymatic potential as key bottom‐up drivers whose relative importance varies with bacterial lifestyle, providing mechanistic insight into biophysical dynamics within river‐confluence ecosystems.

Predicting Summer Precipitation in China: A Hybrid Downscaling Model Using the XGBoost Method - Fan Yue; Xiaojuan Wang; Rong Ai; Yinzhong Wu; Qingquan Li; Guolin Feng (International Journal of Climatology, 2025)
The influencing factors of summer precipitation in China are complex, making prediction challenging, with the need to further improve its forecast accuracy. In the rapid development of machine learning algorithms, a key research topic is how to extract the physical factors that influence summer precipitation in China, and how to effectively integrate these factors with numerical models using machine learning methods to construct prediction models. This study develops a hybrid downscaling model based on the XGBoost method (referred to as the XGBoost model), and evaluates its performance by analysing the potential impacts of circulation and sea surface temperature (SST) anomalies on China's summer precipitation both in the observation and state‐of‐the‐art model. The results indicate that by introducing key climate factors such as sea level pressure (SLP), 500 hPa geopotential height (GH5) from global climate models (GCMs), and SST in the tropical central and eastern Pacific from observation, the XGBoost model can effectively capture the complex nonlinear relationships between large‐scale climate information and local precipitation. Compared with the original results from the BCC_CSM1.1m model, the XGBoost model shows significant improvements in the accuracy of predicting summer precipitation in China. In the cross‐validation for the period of 1994–2016, the anomaly correlation coefficient for summer precipitation increased from −0.001 to 0.34, the RMSE (Root Mean Square Error) reduction rate in most regions exceeded 40%, and the prediction score was significantly improved in most years. The XGBoost model shows obviously better performance than the original model results, validating the potential of the XGBoost method in handling climate data and providing new approaches and insights for regional precipitation prediction.

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Anthropogenic Influence on the Compound Hot and Dry Event in Summer 2022 in the Tibetan Plateau Based on Statistical Downscaling CMIP6 Models - Kening Xue; Wei Li; Siyan Dong; Rong Yu; Leibin Wang (International Journal of Climatology, 2025)
In the summer of 2022, the Tibetan Plateau experienced a record‐breaking compound hot and dry event (CHDE). This study quantifies the contribution of anthropogenic influence to this compound event using a set of high‐resolution statistical downscaling results from six CMIP6 models. The Copula function was used to calculate the joint probability of the compound event. The results show that in the summer of 2022, hot conditions in the Tibetan Plateau broke records since 1961, with a return period of 408 years. The dry conditions were also uncommon, with a return period of 47 years. The hot and dry compound event is particularly rare, with a return period of more than 20,000 years. Based on the results from statistical downscaling models, it was found that anthropogenic influence has increased the risks of dry and hot conditions similar to those in the Tibetan Plateau in 2022 by factors of 3.3 [1.5, 5.2] and 14 [8.6, 21.2], respectively. Additionally, the risk of compound events has been increased by a factor of 46.7 [26.7, 77.6]. In the future, with the intensification of warm‐wet situations on the Tibetan Plateau, the hot conditions similar to 2022 are expected to increase remarkably, with the risk of occurrence rising by factors of 56 [34, 108] and 75 [44, 162] during the periods 2021–2040 and 2051–2070, respectively. Conversely, dry conditions are projected to decrease, with reductions of 0.21 [0.075, 0.46] and 0.51 [0.3, 1.2] times in the two future periods. However, the risk of compound events is expected to increase, with increases of 3.3 [1.5, 5.2] times and 11 [6, 25] times during the two periods. This study is the first to use downscaled simulation to conduct event attribution analysis for the Tibetan Plateau, which can deepen the understanding of the influence of human activities on compound events.

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Rhizosphere shapes the associations between protistan predators and bacteria within microbiomes through the deterministic selection on bacterial communities - Yang Yue; Chen Liu; Boting Xu; Yijin Wang; Qihui Lv; Zeyuan Zhou; Rong Li; George A. Kowalchuk; Alexandre Jousset; Qirong Shen; Wu Xiong (Environmental Microbiology, 2023)
The assembly of bacterial communities in the rhizosphere is well‐documented and plays a crucial role in supporting plant performance. However, we have limited knowledge of how plant rhizosphere determines the assembly of protistan predators and whether the potential associations between protistan predators and bacterial communities shift due to rhizosphere selection. To address this, we examined bacterial and protistan taxa from 443 agricultural soil samples including bulk and rhizosphere soils. Our results presented distinct patterns of bacteria and protistan predators in rhizosphere microbiome assembly. Community assembly of protistan predators was determined by a stochastic process in the rhizosphere and the diversity of protistan predators was reduced in the rhizosphere compared to bulk soils, these may be attributed to the indirect impacts from the altered bacterial communities that showed deterministic process assembly in the rhizosphere. Interestingly, we observed that the plant rhizosphere facilitates more close interrelationships between protistan predators and bacterial communities, which might promote a healthy rhizosphere microbial community for plant growth. Overall, our findings indicate that the potential predator–prey relationships within the microbiome, mediated by plant rhizosphere, might contribute to plant performance in agricultural ecosystems.

High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.

Effect of wheat crop height and canopy coverage on microsprinkling hose irrigation uniformity - Wenjuan Wang; Wene Wang; Rong Wei; Gang Ling; Hong Li; Xiaotao Hu (Irrigation and Drainage, 2023)
Crop shading affects irrigation uniformity and water distribution under microsprinkling hose irrigation (MHI). This study aims to ascertain how MHI distributes irrigation water under crop shading. Various crop heights and canopy coverages of wheat specimens were designed. The experiment was conducted under four working pressures (20, 24, 28 and 32 kPa). The irrigation water distribution of the MHI under crop shading was analysed under various crop heights and canopy coverages. The results showed that (1) the irrigation uniformity of MHI could reach approximately 50% while the planting row spacing of wheat was appropriate. Crop shading had little effect on irrigation performance. (2) During the jointing period, when the wheat height reached 0.4 m, intensive stems reduced the irrigation uniformity and spraying range of MHI. (3) The wheat height could reach 0.6–0.7 m in the maturing period. The uniformity was 25%–50%, which was far lower than the effect of irrigation during the jointing period. To obtain great irrigation performance and acceptable crop yield, it is important to select the proper pressure under the various crop heights and canopy coverages of wheat under MHI.

Characteristics of drought, low temperature, and concurrent events of maize in Songliao Plain - Yunmeng Zhao; Ying Guo; Rui Wang; Kaiwei Li; Guangzhi Rong; Jiquan Zhang; Chunli Zhao (International Journal of Climatology, 2023)
Maize is susceptible to drought and low temperatures. In recent years, drought, low temperatures, and their composite events have often occurred during the growth period of maize, causing a huge impact. In this study, maize in the Songliao Plain was used as the research object. Based on the crop water surplus deficit index (CWSDI) and heat index (F(T)), combined with the Theil–Sen median and Mann–Kendall tests (Sen–MK) and empirical orthogonal function (EOF), the temporal trends and spatial patterns of drought and low temperatures in different growth periods of maize were obtained. Copula modelling was used to analyse the joint probability distribution and return period of drought and low temperatures. The results showed that the temporal variation trend of the CWSDI was significantly different at different growth periods of maize, and there were different trends and spatial modal distributions. However, the temporal variation trend of F(T) was similar, showing a downward trend over the entire region. There was no obvious asymmetry or skew‐dependent structure in the distribution of concurrent events of drought and low temperature; however, the joint probability contours of different growth periods were biased to the upper left. The recurrence period of drought and low‐temperature concurrent events was within 2 years, and the recurrence period was basically between 2 and 5 years, with a reduction in drought or low temperatures.

Spatiotemporal variation of daily precipitation concentration and its potential relationship with climatic factors and land use types in the Haihe River basin, China - Mengyang Ma; Qingming Wang; Yong Zhao; Rong Liu; Enchong Li (International Journal of Climatology, 2023)
Precipitation concentration is a key climatic factor in the hydrologic system. The purpose of this study was to explore the spatiotemporal variation in precipitation concentration and its possible relationship with large‐scale atmospheric circulation and land use types. Based on daily precipitation recorded at 254 stations during 1961–2019 throughout the Haihe River basin (HRB), linear slope and Manner–Kendall trend analysis were used to analyse the spatial variations and trends of the annual daily precipitation concentration index (CI). The Pearson correlation coefficient and cross wavelet analysis were used to evaluate potential correlations between CI and eight climatic factors. Meteorological stations were classified into three land use types: urban type (UT), farmland type (FT), and natural type (NT) using hierarchical clustering, and the impacts of land use types on CI variations and trends were investigated. Annual CI in HRB showed a significant downward trend with a linear rate of −0.0058/decade, and about 210 of the 254 stations had a downtrend, in which 42 stations were at the significance level of 0.05 but did not reach the significance level of 0.01, and 52 stations are at the 0.01 significance level. The East Asian monsoon index (EASMI), South Asian monsoon index (SASMI), South China Sea monsoon index (SCSMI), and Southern Oscillation Index (SOI) were positively correlated with CI, whereas the Pacific Decadal Oscillation (PDO), Multivariate ENSO index (MEI), and Western Pacific index (WP) were negatively correlated. The Sunspot index (SS) had a significant resonance period of 9–14‐year with CI. EASMI and ENSO events were the dominant factors driving CI trends. The negative CI trends of UT were more significant than those of FT and NT, with linear slope gaps of −0.0041/decade (UT versus FT) and −0.0064/decade (UT vs. NT), respectively.

Eutrophication and predation mediate zooplankton diversity and network structure - Yun Li; Rong Wang; Haojie Su; Jianjun Wang; Ping Xie; Feizhou Chen (Limnology and Oceanography, 2022)
Anthropogenic activities such as eutrophication and fishing have prominent effects on freshwater ecosystems. However, the ways in which ecosystem function and biodiversity respond to multiple drivers from eutrophication and top‐down predation remains inconclusive. We studied zooplankton communities in 102 subtropical shallow lakes in the eastern plain of China and further examined the joint effects of nutrient enrichment and predation on biodiversity and ecological networks. We found that alpha diversity was negatively influenced by nutrient conditions (such as total phosphorus and total nitrogen [TN]), whereas beta diversity (β‐diversity) was positively related to nutrients and was also structured by omnivorous fish showing a unimodal pattern. Furthermore, the network skewness of zooplankton increased with nutrient enrichment, especially TN, and was negatively related to omnivorous fish. This skewness is more sensitive than β‐diversity, whereas negative skew is primarily caused by omnivorous fish. Our results demonstrated that top‐down effects were dominant for zooplankton communities and resulted in structural adjustment of zooplankton communities, mainly with an increase in fish predation. A negative skewed network indicates the presence of more generalist species and stronger connections among the zooplankton assemblages, as well as decreased β‐diversity.

Use of historical and contemporary distribution of mammals in China to inform conservation - Kang Huang; He Zhang; Chengliang Wang; Rong Hou; Pei Zhang; Gang He; Songtao Guo; Shiyi Tang; Baoguo Li; Charles Oxnard; Ruliang Pan (Conservation Biology, 2021)
A systematic understanding of dynamic animal extinction trajectories for different regions in a nation like China is critically important to developing practical conservation strategies. We explored historical and contemporary changes in terrestrial mammalian diversity to determine how diversity in each of the 5 regions in China has changed over time and to examine the conservation potential of these regions. We used records from databases on Pleistocene mammalian fossils and historical distribution records (1175–2020) for Primates (as a case study) to reconstruct evolutionary and historical distribution trajectories of the 11 orders of terrestrial mammals and to predict their prospective survival based on the national conservation strategy applied. The results indicated that since the Pleistocene, 4–5 mammalian orders have been lost in the northeast, 3 in central China, 2 along the coast, and 1 in the northwest. In the southwest, all 11 orders were maintained. Contemporarily, the coast and southwest had the highest and second‐highest species densities. The southwest region and southeastern sections of the northwest region were the most historically and contemporarily diverse areas, which suggests that they should be the first priority for protected area (PA) designation. The central and coastal areas should be secondarily prioritized. In these 2 regions, conservation should focus on human coexistence with nature. Less attention should be paid to the PA in the northeast and western northwest because in these areas ecosystems are depauperate and the climate is harsh. Conservation in these areas should focus principally on avoiding further human encroachment on natural areas. Article impact statement : Historical and contemporary patterns of extinction can be a basis for mammalian conservation strategies.

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs - Liangming Chen; Rong Huang; Denghui Zhu; Cheng Yang; Libo He; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Journal of Fish Biology, 2019)
This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30,538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P dmrt4a ( P cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.

Changes in gene and genotype frequencies during the development of the grass carp Ctenopharyngodon idella - LiB. He; Lv Xiong; AiD. Zhang; YongM. Li; Rong Huang; LanJ. Liao; ZuoY. Zhu; YaP. Wang (Journal of Fish Biology, 2018)
In this study, a full‐sib population of Ctenopharyngodon idella was constructed and approximately 500 C. idella individuals were sampled at four early developmental stages (hatching, first feeding, juvenile fish and young fish). Four DNA pools were constructed and subjected to next‐generation sequencing. On the basis of the identification of single nucleotide polymorphisms (SNP), changes in gene and genotype frequencies during the developmental progress of C. idella were revealed, which indicates that death during the early developmental stage is not a random process. These findings will establish the basis for further studies performed for identifying superior alleles or genotypes as target markers for molecular breeding.

Analysis of slight precipitation in China during the past decades and its relationship with advanced very high radiometric resolution normalized difference vegetation index - Xinyue Li; Yves Balkanski; Zhengfang Wu; Thomas Gasser; Philippe Ciais; Feng Zhou; Laurent Li; Shu Tao; Shushi Peng; Shilong Piao; Rong Wang; Tao Wang; et al. (International Journal of Climatology, 2018)
Precipitation is one of the most important factors determining the occurrence of extreme hydro‐meteorological events and water resource availability. Precipitation in different grades has diverse ecological effects, and slight precipitation (SP, defined as 0.1–1.0 mm/day) is the minimal level among them. In this study, we investigated SP trends from 1961 to 2013, as well as the relationship between SP and advanced very high radiometric resolution (AVHRR) normalized difference vegetation index (NDVI) in China during growing season from 1981 to 2006. The distributions and trends of SP were analysed by calculating the daily precipitation data. The average annual slight precipitation amount (SPA) and the number of slight precipitation days (SPD), derived from 839 monitoring stations in China, show a decreasing trend over the last five decades, which is in agreement with total precipitation (TP) but in different rates. When the trend was analysed seasonally, SP in most stations decreases significantly in September–October–November (SON) and June–July–August (JJA), and the largest decrease is found in SON. About 49.5 and 68.7% of monitoring stations show a decreasing trend in SON, in both SPA and SPD, whereas the trend is less popular in March–April–May (MAM, SPA: 19.7%, SPD: 41.4%) and December–January–February (JJF, SPA: 25.6%, SPD: 43.1%). Moreover, our analysis indicates that the decrease of SP is mainly due to the decrease of SPD as the median amount of daily SP was unchanged over the past five decades (close to 0.3 mm/day). Based on 26‐year (1981–2006) semi‐monthly AVHRR NDVI data and the records of SP data, the relationship between AVHRR NDVI and SP was also investigated. In regions with lower (

Srk1 kinase, a SR protein‐specific kinase, is important for sexual reproduction, plant infection and pre‐mRNA processing in Fusarium graminearum - Guanghui Wang; Peng Sun; Ziwen Gong; Lianfeng Gu; Yi Lou; Wenqin Fang; Lianhu Zhang; Li Su; Tao Yang; Baohua Wang; Jie Zhou; Jin‐Rong Xu; et al. (Environmental Microbiology, 2018)
Summary SR protein‐specific kinases (SRPKs) uniquely with a spacer region are important splicing factors from yeast to human. However, little is known about their biological functions in filamentous fungi. Therefore, we characterized a SRPK called SRK1 in wheat scab fungus Fusarium graminearum . Our data showed that Srk1 is required for vegetative growth, sexual reproduction and plant infection, and plays critical roles in pre‐mRNA alternative splicing and gene expression. Remarkably, we found that Srk1 displayed dynamic shuttling between cytoplasm and the nucleus, which is regulated by the divergent spacer domain rather than its kinase activity, suggesting a regulatory mechanism for Srk1. Interestingly, Srk1‐GFP also localized to the septal pores, indicating a possible role of Srk1 unrelated to mRNA processing. Although both K1 and K2 lobes of the kinase domain are essential for Srk1 functions, the K2 but not K1 lobe is responsible for the septal pore localization. Lastly, we established that Srk1 physically interacts with the two SR proteins, FgNpl3 and FgSrp1. Overall, our results indicated that SRK1 regulates fungal development, plant infection and mRNA processing by phosphorylation of other splicing factors including SR proteins, and the spacer domain regulates the functions of Srk1 by modulating its nucleocytoplasmic shuttling.

Global forest carbon uptake due to nitrogen and phosphorus deposition from 1850 to 2100 - Rong Wang; Daniel Goll; Yves Balkanski; Didier Hauglustaine; Olivier Boucher; Philippe Ciais; Ivan Janssens; Josep Penuelas; Bertrand Guenet; Jordi Sardans; Laurent Bopp; Nicolas Vuichard; et al. (Global Change Biology, 2017)
Spatial patterns and temporal trends of nitrogen (N) and phosphorus (P) deposition are important for quantifying their impact on forest carbon (C) uptake. In a first step, we modeled historical and future change in the global distributions of the atmospheric deposition of N and P from the dry and wet deposition of aerosols and gases containing N and P. Future projections were compared between two scenarios with contrasting aerosol emissions. Modeled fields of N and P deposition and P concentration were evaluated using globally distributed in situ measurements. N deposition peaked around 1990 in European forests and around 2010 in East Asian forests, and both increased sevenfold relative to 1850. P deposition peaked around 2010 in South Asian forests and increased 3.5‐fold relative to 1850. In a second step, we estimated the change in C storage in forests due to the fertilization by deposited N and P (∆C ν dep ), based on the retention of deposited nutrients, their allocation within plants, and C:N and C:P stoichiometry. ∆C ν dep for 1997–2013 was estimated to be 0.27 ± 0.13 Pg C year −1 from N and 0.054 ± 0.10 Pg C year −1 from P, contributing 9% and 2% of the terrestrial C sink, respectively. Sensitivity tests show that uncertainty of ∆C ν dep was larger from P than from N, mainly due to uncertainty in the fraction of deposited P that is fixed by soil. ∆ C P dep was exceeded by ∆ C N dep over 1960–2007 in a large area of East Asian and West European forests due to a faster growth in N deposition than P. Our results suggest a significant contribution of anthropogenic P deposition to C storage, and additional sources of N are needed to support C storage by P in some Asian tropical forests where the deposition rate increased even faster for P than for N.

Activation of the signalling mucin MoM sb2 and its functional relationship with C bp1 in M agnaporthe oryzae - Guanghui Wang; Guotian Li; Shijie Zhang; Cong Jiang; Jun Qin; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary Various surface signals are recognized by M agnaporthe oryzae to activate the P mk1 MAP kinase that is essential for appressorium formation and invasive growth. One of upstream sensors of the P mk1 pathway is the MoM sb2 signalling mucin. However, the activation of MoM sb2 and its relationship with other sensors is not clear. In this study, we showed that the cleavage and transmembrane domains are essential for MoM sb2 functions. Cleavage of MoM sb2 was further confirmed by western blot analysis, and five putative cleavage sites were functionally characterized. Expression of the extracellular region alone partially rescued the defects of M omsb2 in appressorium formation and virulence. The cytoplasmic region of MoM sb2, although dispensable for appressorium formation, was more important for penetration and invasive growth. Interestingly, the M omsb2 cbp1 double mutant deleted of both mucin genes was blocked in P mk1 activation. It failed to form appressoria on artificial surfaces and was non‐pathogenic. In addition, we showed that MoM sb2 interacts with R as2 but not with MoC dc42 in co‐immunoprecipitation assays. Overall, results from this study indicated that the extracellular and cytoplasmic regions of MoM sb2 have distinct functions in appressorium formation, penetration and invasive growth, and MoM sb2 has overlapping functions with C bp1 in recognizing environmental signals for P mk1 activation.

The MADS ‐box transcription factor FgMcm1 regulates cell identity and fungal development in F usarium graminearum - Cui Yang; Huiquan Liu; Guotian Li; Meigang Liu; Yingzi Yun; Chenfang Wang; Zhonghua Ma; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary In eukaryotic cells, MADS ‐box genes are known to play major regulatory roles in various biological processes by combinatorial interactions with other transcription factors. In this study, we functionally characterized the FgMCM1 MADS ‐box gene in F usarium graminearum , the causal agent of wheat and barley head blight. Deletion of FgMCM1 resulted in the loss of perithecium production and phialide formation. The F gmcm1 mutant was significantly reduced in virulence, deoxynivalenol biosynthesis and conidiation. In yeast two‐hybrid assays, FgMcm1 interacted with M at1‐1‐1 and F st12, two transcription factors important for sexual reproduction. Whereas F gmcm1 mutants were unstable and produced stunted subcultures, F gmcm1 mat1‐1‐1 but not F gmcm1 fst12 double mutants were stable. Furthermore, spontaneous suppressor mutations occurred frequently in stunted subcultures to recover growth rate. Ribonucleic acid sequencing analysis indicated that a number of sexual reproduction‐related genes were upregulated in stunted subcultures compared with the F gmcm1 mutant, which was downregulated in the expression of genes involved in pathogenesis, secondary metabolism and conidiation. We also showed that culture instability was not observed in the F vmcm1 mutants of the heterothallic F usarium verticillioides . Overall, our data indicate that FgMcm1 plays a critical role in the regulation of cell identity, sexual and asexual reproduction, secondary metabolism and pathogenesis in F . graminearum .

A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.

Comments on ‘Influences of the Bermuda High and atmospheric moistening on changes in summer rainfall in the Atlanta, Georgia region, USA ’ - Wenhong Li; Laifang Li; Rong Fu; Yi Deng; Hui Wang (International Journal of Climatology, 2013)
In a recent article, Diem (2012) examined the impact of the North Atlantic Subtropical High ( NASH ) and atmospheric moistening on summer rainfall variability in the Atlanta, Georgia region. In his paper, he indicated that the results concerning the variability of the NASH western ridge discussed in Li et al . (2011) are incorrect. We present new evidence here to show that the comments by Diem (2012) are unjustified; the main conclusions in Li et al . (2011) were drawn according to the data over a 60‐year (1948–2007) and 45‐year (1958–2002) periods of NCEP / NCAR and ERA ‐40 reanalysis, whereas conclusions of Diem (2011) were based upon the trend analysis of a similar but different index of the NASH using sub‐periods of 1948–2009 (since late 1970s). The comment emphases the importance of climate dynamics to study precipitation variability over the Southeastern US and further strengthens the conclusions originally put forth in Li et al . (2011): over the last 60 years (1948–2007), the NASH has shown a significant trend of westward movement, and the meridional movement of the NASH western‐ridge (i.e. its latitudinal change) has enhanced in the recent three decades.

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Single cysteine substitution in Bacillus thuringiensis Cry7Ba1 improves the crystal solubility and produces toxicity to Plutella xylostella larvae - Donghai Peng; Fenshan Wang; Nisha Li; Zhenyu Zhang; Rong Song; Zimin Zhu; Lifang Ruan; Ming Sun (Environmental Microbiology, 2011)
Summary Many Bacillus thuringiensis isolates have no demonstrated toxicity against insects. In this study, a novel holotype crystal protein gene cry7Ba1 was isolated from a ‘non‐insecticidal’ B. thuringiensis strain YBT‐978. The Cry7Ba1 protein showed high toxicity against Plutella xylostella larvae after the crystals were dissolved at pH 12.5, suggesting that the ‘non‐insecticidal’ properties of this protein were due to insolubility in the normal insect midgut pH environment. After the C‐terminal half of Cry7Ba1 was replaced by that of Cry1Ac or Cry1C proteins, the recombinant protein inclusions could be dissolved at pH 9.5, and exhibited high toxicity against P. xylostella larvae. This result proved the insolubility of Cry7Ba1 crystal was determined by the structure of its C‐terminal half. Further, six mutations were constructed by substituting cysteine residues with serine. Solubility studies showed that the crystals from mutants C697S, C834S and C854S could be dissolved at lower pH (10.5, 9.5 and 11.5 respectively). Bioassays showed that crystals from mutant C834S were toxic to P. xylostella larvae. Our discoveries suggest that a single cysteine residue located in the C‐terminal half of the protein determines the solubility and toxicity of some nontoxic crystal proteins. This study provides a strategy to isolate novel insecticidal crystal protein genes from ‘non‐insecticidal’ B. thuringiensis strains.

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Feeding activities of zooplankton in the Bohai Sea - RONG WANG; CHAOLUN LI; KE WANG; WUCHANG ZHANG (Fisheries Oceanography, 1998)
The Bohai Sea was the site of the Chinese national GLOBEC programme. During the June 1997 cruises of R/V Science No.1 , observations and experiments on zooplankton feeding were conducted. At five 48 h time‐series stations the following observations and measurements on zooplankton were carried out: (1) diurnal vertical migration, by collecting samples at different layers every 3 h with a closing net; (2) diurnal feeding rhythms, by gut pigment analysis; and (3) ingestion rate, by both gut pigment analysis and the dilution method. A classification by body size was used to deal with the diversity of species and developmental stages of zooplankton assemblages. Samples were separated into three size groups: small (200–500 μm), medium (500–1000 μm) and large (> 1000 μm). The results showed that the copepods ( Calanus sinicus, Paracalanus parvus, Acartia bifilosa and Centropages mcmurrichi ) performed clear diurnal vertical migrations. However, their behaviour was different at different stations. The variation in gut pigment content over the 24 h cycle showed strong diurnal feeding rhythms, particularly for the large size group. Gut pigment contents reached their daily maximum during the time from dusk to midnight (18:00–24:00). The peak value was about 10 times the minimum observed in the daytime. The in situ daily grazing rate, based on gut pigment contents and evacuation experiments, was 4.00–12.65 ng chl a ind −1 day −1 for the small size group, 5.99–66.58 ng chl a ind −1 day −1 for the medium size group and 31.31–237.13 ng chl a ind −1 day −1 for the large size group. The copepods consumed only a small part (2.90–13.52%) of the phytoplankton biomass but about 77% of the daily production. The grazing mortality rate of phytoplankton by microzooplankton ( −1 The calculated daily consumption of phytoplankton biomass was 35–50%, and 85–319% of the potential production.